2012
DOI: 10.1097/cji.0b013e31824d72ee
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of the TGF-β1 Gene Increases the Immunogenicity of Cells From Human Ovarian Carcinoma

Abstract: Cells from many tumors produce transforming growth factor (TGF)-βwhich facilitates their escape from control by the immune system. We previously reported that non-immunogenic cells from either of two transplantable mouse tumors became effective as therapeutic tumor vaccines after lentivirus-mediated shRNA interference to ‘silence’the TGF-β1 gene. We now show that cells from in vitro cultured human ovarian carcinomas (OvC) make large amounts of TGF-β1 and that this can be prevented by ‘silencing’ the TGF-β1 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Similar to TGF-β1, the supernatant derived from SKOV3 cells could convert part of freshly isolated CD4 + /CD25 − T cells into CD25 + population with characters as CD4 + /CD25 + /FoxP3 + Treg cells. Knockdown TGF-β1 gene increases the immunogenicity of human EOC cells and impairs the tumorigenic ability of human EOC cells [ 36 , 37 ]. The role of VEGF in tumor angiogenesis has been well characterized, nevertheless, it is also known to have an immunosuppressive activity besides its angiogenic role and to promote tumor immune escape by impairing DC maturation and antitumour T cell activation in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to TGF-β1, the supernatant derived from SKOV3 cells could convert part of freshly isolated CD4 + /CD25 − T cells into CD25 + population with characters as CD4 + /CD25 + /FoxP3 + Treg cells. Knockdown TGF-β1 gene increases the immunogenicity of human EOC cells and impairs the tumorigenic ability of human EOC cells [ 36 , 37 ]. The role of VEGF in tumor angiogenesis has been well characterized, nevertheless, it is also known to have an immunosuppressive activity besides its angiogenic role and to promote tumor immune escape by impairing DC maturation and antitumour T cell activation in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…HE4, human epididymis factor 4 [25], which is expressed by OvC, particularly its serous type [26, 27], and in lung adenocarcinoma [28] is attracting attention as a diagnostic marker which can complement CA125 since it is less often elevated in benign conditions and can be applied in combination with CA125 to aid diagnosis of women with a pelvic mass [20, 29-31]. It may also be a therapeutic target since it can be recognized by Th1 type lymphocytes, including cytolytic T cells [32]. …”
Section: Introductionmentioning
confidence: 99%
“…CSF1R is overexpressed in OC and the determination of its circulating levels proved useful for disease detection and the evaluation of therapeutic e cacy [67]. It has been reported that the cells of ovarian carcinoma produce large amounts of TGF-β1, which facilitates their escape from the immune system, and the clinical e cacy of immunotherapy based on TGF-β1-silenced tumor vaccines for OC has been investigated [68]. We speculate that UBE2T overexpression may cause the reduction or depletion of immune cells, leading to tumor progression by immune escape.…”
Section: Discussionmentioning
confidence: 99%